2021
DOI: 10.3390/ijms23010101
|View full text |Cite
|
Sign up to set email alerts
|

FvMYB79 Positively Regulates Strawberry Fruit Softening via Transcriptional Activation of FvPME38

Abstract: Strawberry is a soft fruit with short postharvest life, due to a rapid loss of firmness. Pectin methylesterase (PME)-mediated cell wall remodeling is important to determine fruit firmness and softening. Previously, we have verified the essential role of FvPME38 in regulation of PME-mediated strawberry fruit softening. However, the regulatory network involved in PME-mediated fruit softening is still largely unknown. Here, we identified an R2R3-type MYB transcription factor FvMYB79, which activates the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…A similar positive regulatory feedback loop has also been reported for ABA and a MYB transcription factor, FvMYB79 , which is positively regulated by ABA. Thus, FvMYB79 silencing decreases the ABA content and delays fruit ripening, a phenotype that could not be reverted even after ABA treatment ( Cai et al., 2022 ). Another MYB transcription factor FaGAMYB has been shown to be an important regulator of strawberry fruit ripening, as it induces ABA biosynthesis by regulating NCED1 and NCED2 , as well as ABI5 and DREB1 , two TFs involved in ABA signaling.…”
Section: Phytohormones In Strawberry Fruit Development and Ripening R...mentioning
confidence: 99%
See 4 more Smart Citations
“…A similar positive regulatory feedback loop has also been reported for ABA and a MYB transcription factor, FvMYB79 , which is positively regulated by ABA. Thus, FvMYB79 silencing decreases the ABA content and delays fruit ripening, a phenotype that could not be reverted even after ABA treatment ( Cai et al., 2022 ). Another MYB transcription factor FaGAMYB has been shown to be an important regulator of strawberry fruit ripening, as it induces ABA biosynthesis by regulating NCED1 and NCED2 , as well as ABI5 and DREB1 , two TFs involved in ABA signaling.…”
Section: Phytohormones In Strawberry Fruit Development and Ripening R...mentioning
confidence: 99%
“…Besides the knowledge of how all these different TFs regulate hormone biosynthesis and signaling ( Figure 1A ), several studies have also reported how some TFs are in turn regulated by different hormones ( Table 1 ) ( Encinas-Villarejo et al., 2009 ; Tisza et al., 2010 ; Daminato et al., 2013 ; Medina-Puche et al., 2015 ; Medina-Puche et al., 2016 ; Molina-Hidalgo et al., 2017 ; Carrasco-Orellana et al., 2018 ; Lu et al., 2018 ; Moyano et al., 2018 ; Medina-Puche et al., 2019 ; Xie et al., 2020 ; Zhang et al., 2020 ; Martín-Pizarro et al., 2021 ; Cai et al., 2022 ; Wang et al., 2022 ), highlighting the complex regulatory network between hormones and transcriptional regulators to control strawberry fruit development and ripening.…”
Section: Phytohormones In Strawberry Fruit Development and Ripening R...mentioning
confidence: 99%
See 3 more Smart Citations